Fading Foundations: Probability and the Regress Problem - Atkinson, David; Peijnenburg, Jeanne (Cham Springer Nature, 2017)
epistemic justification; infinite regress; epistemology; ethics; metaphysics; philosophy
Nederlandse Organisatie voor Wetenschappelijk Onderzoek
English
Keywords: Philosophy; epistemic justification; infinite regress; epistemology; ethics; metaphysics; philosophy